LENGTH - WEIGHT RELATIONSHIP OF TILAPIA MOSSAMBICUS OF IDUKKI RESERVOIR - NAIR, P GOPINATHAN (Fishery Technology, 2017)
The results of ten months study (September 1983 to July 1984) of the length-weight relationship of males and females of Tilapia mossambicus of the reservoir waters of Idukki Hydel Project show deviation from the cubic relationship of these two parameters. This is due to the retarded growth pattern of this exotic species in this oligotrophic habitat.